2016
DOI: 10.1016/j.scriptamat.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Porosity regrowth during heat treatment of hot isostatically pressed additively manufactured titanium components

Abstract: Available online xxxx X-ray computed tomography has been used to track the behaviour of individual pores found in selective electron beam melted additive manufactured titanium. Porosity was found to shrink below the detection limit of X-ray microtomography (b5 μm) upon hot isostatic pressing. Spherical argon containing gas pores, which have a high internal gas pressure following hot isostatic pressing, have been found to progressively reappear and grow in proportion to their original as-built size during high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(89 citation statements)
references
References 12 publications
6
83
0
Order By: Relevance
“…Additive manufacturing processes often produce microstructures with internal pores of various shapes and sizes that are detrimental to fatigue performance . Postprocessing techniques (ie, hot‐isostatic pressing [HIP'ing]) may be employed to close pores, but HIP'ing adds cost, alters the microstructure, relieves engineered residual stresses, and may not close all pores . Consequently, it may be beneficial to provide models to relate the fatigue life reduction from pores to pore size, pore shape, loading, and other fatigue life parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing processes often produce microstructures with internal pores of various shapes and sizes that are detrimental to fatigue performance . Postprocessing techniques (ie, hot‐isostatic pressing [HIP'ing]) may be employed to close pores, but HIP'ing adds cost, alters the microstructure, relieves engineered residual stresses, and may not close all pores . Consequently, it may be beneficial to provide models to relate the fatigue life reduction from pores to pore size, pore shape, loading, and other fatigue life parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Postbuild treatments such as hot isostatic pressing (HIP) have been frequently applied to AM parts and have demonstrated, by some studies, effective in removing the pores from the metal parts . However, other studies have shown that HIP's effectiveness is inconsistent across various AM platforms . HIP's reduced performance in laser AM parts is likely due to the presence of nonsoluble Ar gas in the pores .…”
Section: Introductionmentioning
confidence: 99%
“…2,11,[22][23][24] However, other studies have shown that HIP's effectiveness is inconsistent across various AM platforms. 11,[24][25][26][27] HIP's reduced performance in laser AM parts is likely due to the presence of nonsoluble Ar gas in the pores. 28 Recent high-resolution X-ray CT studies 24,26 indirectly confirmed the existence of pressurized pores in HIP'ed laser AM parts by noting the regrowth of them during the secondary heat treatment (HT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, X-ray computed tomography has been widely applied to material science and engineering [9][10][11] and some researchers began to use this technology to analyze the powder-binder separation [12,13], because of its obvious advantages, including 3D and the non-destructive characterization of the spatial structure. In the previous studies, powder-binder separation was analyzed by using gray value distribution in the CT reconstructed data [14,15].…”
Section: Introductionmentioning
confidence: 99%